2012
DOI: 10.1063/1.4768814
|View full text |Cite
|
Sign up to set email alerts
|

First-principles study of transition metal doped Li2S as cathode materials in lithium batteries

Abstract: The effects of transition metal (TM) doping on Li-vacancy formation energies and electrode potentials of Li2S cathode materials for lithium batteries are investigated using first-principles calculations with density functional theory. In addition, the geometric and electronic structures for 1.56 at. % Fe-doped lithium sulfide are analyzed to further reveal the TM-doping effect. We find that Evac can be only moderately enhanced by the increasing atomic number of TM dopant. The Evac is lowered from 3.37 eV in pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 45 publications
4
20
0
Order By: Relevance
“…9 In order to improve the electrochemical performance of the cathode, some kind of transition metals (TM), such as Fe, Co, Ni, and Cu may be added to the cathode materials to activate the insulating Li 2 S. [10][11][12][13][14] Luo et al studied TM-doped Li 2 S by a first-principles approach, and it was found that the electronic conductivity can be increased by Li vacancies, and that dopants can lower the vacancy formation energy. 15 They also pointed out that metal-induced gap states (MIGS) are helpful for electronic conductivity. 15 The cathode architecture plays an important role in determining the performance of the Li-S battery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 In order to improve the electrochemical performance of the cathode, some kind of transition metals (TM), such as Fe, Co, Ni, and Cu may be added to the cathode materials to activate the insulating Li 2 S. [10][11][12][13][14] Luo et al studied TM-doped Li 2 S by a first-principles approach, and it was found that the electronic conductivity can be increased by Li vacancies, and that dopants can lower the vacancy formation energy. 15 They also pointed out that metal-induced gap states (MIGS) are helpful for electronic conductivity. 15 The cathode architecture plays an important role in determining the performance of the Li-S battery.…”
Section: Introductionmentioning
confidence: 99%
“…15 They also pointed out that metal-induced gap states (MIGS) are helpful for electronic conductivity. 15 The cathode architecture plays an important role in determining the performance of the Li-S battery. 16 A wide variety of microstructures have been synthesized to develop the performance of the battery.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have investigated the influence of monodisperse metal and N co-doping on the suppression of the shuttle, and used it in LSBs successively. As early as 2012, Luo et al studied Li 2 S doped with transition metals in lithium battery cathodes, which opened the door to transition metal-doped graphene as lithium battery cathodes [ 101 ]. Zhang et al used first-principles simulations to study the interaction between Fe and N co-doped graphene (FeN 4 @graphene) [ 89 ].…”
Section: Heteroatom Doped Graphenementioning
confidence: 99%
“…A systematic study of Li + transport in Li 2 S, conducted by S. Lorger et al, led to the conclusion that the ion conduction is governed by Frenkel disorder and vacancy-dopant association [12]. Density functional theory calculations were employed to stimulate the effect of transition metal doping on the Li 2 S properties, and it was found that Fe doping resulted in a reduction of the Li vacancy formation energy and the induction of a gap state, which then resulted in the accommodation of an electron during extraction / insertion of a Li ion [13]. We have previously reported that a slightly reduced amount of Li 2 S in Li 7 P 2 S 8 I results in an increase of the ionic conductivity owing to the formation of a lithium vacancy structure [14,15].…”
Section: Introductionmentioning
confidence: 99%